Adaptive Data Hiding, Using Pixel-Value-Differencing and LSB Substitution. Issue 8 (16th November 2016) - Khodaei, Masoumeh; Sadeghi Bigham, Bahram; Faez, Karim
ABSTRACT: With the development of Internet communications, the security of message sending on the Internet has become very important. This article proposes a new adaptive data hiding method with a large data-embedding capacity for gray-scale images to raise the security of sending a message between sender and receiver in networks. At first, the image is divided into some blocks consisting of two consecutive pixels. If the values of both pixels are small, fewer secret bits will be embedded within the two pixels, otherwise, the difference value of two pixels is calculated, and according to the obtained difference value, the method will estimate the number of embedding bits into LSBs of two pixels. This number is adaptive and depends on the range to which the difference value belongs. A readjusting phase is presented to keep the difference of value pixels in the same range before and after embedding. Experimental results show that our method has increased the capacity of embedding bits in comparison with the several other methods.